2008 IEEE Conference on Robotics, Automation and Mechatronics 2008
DOI: 10.1109/ramech.2008.4681431
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Hysteresis in Pleated Pneumatic Artificial Muscles

Abstract: Estimating the force exerted by a pneumatic muscle actuator by measuring its gauge pressure is challenging since hysteresis is almost always present. This paper investigates the hysteresis phenomenon in Pleated Pneumatic Artificial Muscles, which is found to be largely independent of gauge pressure. A Preisach based hysteresis model that can cope with the specific shape of the force-contraction characteristic of pneumatic muscles is proposed, and its results are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…For an accurate hysteresis loop model of a PAM, Van Damme et al [13] used a Preisach model for the hysteresis in a pleated PAM. The weighted superposition of elementary relay hystereses represents the output of the Preisach model.…”
Section: Introductionmentioning
confidence: 99%
“…For an accurate hysteresis loop model of a PAM, Van Damme et al [13] used a Preisach model for the hysteresis in a pleated PAM. The weighted superposition of elementary relay hystereses represents the output of the Preisach model.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent research on this matter shows, that a hysteresis behaviour of the PAMs has been ascertained in [12] and [19]. It is demonstrated that the tube's rubber shell does not only deform elastically, but also plastically.…”
Section: Discussionmentioning
confidence: 95%
“…Kwok et al (2007) established a hysteresis model based on hyperbolic tangent non-linear function to improve the model precision of magnetorheological fluid dampers. Van Damme et al (2008) proposed a Preisach based hysteresis model to solve the specific shape of the force-contraction characteristic of pneumatic muscles. Ruderman et al (2009) designed a novel approach which combines distributed Preisach model and generalized MaxwellSlip friction model to explore elastic robot joints with hysteresis and backlash.…”
Section: Introductionmentioning
confidence: 99%